Functional outcome of Austin Moore Hemire Placement Arthroplasty in Fracture Neck of Femur in elderly - Dawadi, Tej P.; Bhatta, TR; Gyawali, B; Adhikari, BR; Giri, SK (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Objective: To study the outcome of Austin Moore Hemireplacement Arthroplasty in terms of Harris Hip Score and Mobility and Aid Score in fracture neck of femur in elderly. Design: A prospective randomized study carried out between September 2011 to August 2012 AD. Methods: We performed 30 Austin Moore hemiarthroplasties in patients aged 65 and above that sustained a displaced femoral neck fracture and evaluated the outcome in terms of Harris Hip Score and Mobility and Aid Score. Results: Mean HHS at 2 week was 63.93 which increased to 73.83, 80.53 and 86.48 at 6 weeks, 12 weeks and 6 months respectively with overall excellent to good result of 60%. The mean MASM at 6 months was 4.0 whereas the pre-injury MASM was 4.53. Conclusion: Hemiarthroplasty with Austin Moore Prosthesis is safe and effective method of treatment for displaced fracture neck of femur in elderly. There was early post-operative full weight bearing mobilization with reduction in major complications. The operative duration, post-operative complicationsare comparable to other similar studies done elsewhere. The end functional results also depend on the associated comorbidities and optimum post op rehabilitation. Journal of Manmohan Memorial Institute of Health Sciences Vol. 3, No. 1, 2017, page: 6-15